Understanding Marcel Proust - Thiher, Allen, 1941- (Understanding modern European and Latin American literature., 2013)
This book includes an overview of Proust's development as a writer, addressing both works published and unpublished in his lifetime, and then offers an in-depth interpretation of Proust's major novel, In Search of Lost Time, relating it to the Western literary tradition while also demonstrating its radical newness as a narrative. In this book, the author outlines Proust's development in the context of the political and artistic life of the Third Republic, arguing that everything Proust wrote before In Search of Lost Time was an experiment in sorting out whether he wanted to be a writer of critical theory or of fiction. Ultimately, the author observes, all these experiments had a role in the elaboration of the novel. Proust became both theorist and fiction writer by creating a bildungsroman narrating a writer's education.